The peculiarities of the ultrastructure of frontal cortex and hippocampus of rats in conditions of experimental allergic encephalomyelitis. - A. A. Nefodov; V. I. Mamchur; I. V. Tverdokhleb (Морфологія, 2016)
Background. Multiple sclerosis refers to the demyelinating diseases of the nervous system, in which the main pathological changes develop in the white matter and are characterized by disintegration of myelin sheaths of conductive systems in different parts of the brain and spinal cord. Objective. To assess the degree of ultrastructural changes of frontal cortex and hippocampus of rats in conditions of experimental allergic encephalomyelitis. Methods. The research was conducted on 14 white rats divided randomly in 2 groups: group 1 – intact animals; group 2 – rats with experimental allergic encephalomyelitis. Experimental allergic encephalomyelitis was induced in 8 animals of the experimental group single subcutaneous inoculation encephalitogenic mixture in full adjuvant of Freynd at the rate of 100 mg homogenate of homologous spinal cord, 0.2 ml puff (the content of killed mycobacteria 5 mg/ml) and 0.2 ml of physiological solution on the animal. Transmission electron microscopy was performed on the 14th day of encephalitogenic mixture administration. Results. In the frontal cortex and hippocampus experimental allergic encephalomyelitis induces apoptosis of the neurocytes with disruption of the structure of mitochondria (increase in size, the fragmentation of the outer membrane, destruction of cristae), disseminated perineuronal edema of the brain substance, violation of the structure of most axo-somatic synapses, the demyelination of nerve conductors with signs of fragmentation of neurofibril. Conclusion. The single subcutaneous inoculation of encephalitogenic mixture in full adjuvant of Freynd leads to the development of multifocal demyelination and axonal degeneration in the hippocampus and frontal cortex of experimental animals.